Significance of mannose-binding lectin deficiency and nucleotide-binding oligomerization domain 2 polymorphisms in Staphylococcus aureus bloodstream infections: a case-control study. - Michael Osthoff; Hue Mun Au Yong; Melinda M Dean; Damon P Eisen (PLoS ONE, 2013)
BACKGROUND: Pathways coordinated by innate pattern recognition receptors like mannose-binding lectin (MBL) and nucleotide-binding oligomerization domain 2 (NOD2) are among the first immune responses to Staphylococcus aureus (S. aureus) bloodstream infections (BSI) in animal models, but human data are limited. Here, we investigated the role of MBL deficiency and NOD2 mutations in the predisposition to and severity of S. aureus BSI. PATIENTS AND METHODS: A matched case-control study was undertaken involving 70 patients with S. aureus BSI and 70 age- and sex-matched hospitalized controls. MBL levels, MBL2 and NOD2 polymorphisms were analyzed. RESULTS: After adjusting for potential confounders, MBL deficiency (<0.5 µg/ml) was found less frequently in cases than controls (26 vs. 41%, OR 0.4, 95% confidence interval (CI) 0.20-0.95, p=0.04) as were low producing MBL genotypes (11 vs. 23%, OR 0.2, 95% CI 0.08-0.75, p=0.01), whereas NOD2 polymorphisms were similarly distributed. Cases with NOD2 polymorphisms had less organ dysfunction as shown by a lower SOFA score (median 2.5 vs. 4.5, p=0.02), whereas only severe MBL deficiency (<0.1 µg/ml) was associated with life-threatening S. aureus BSI (OR 5.6, 95% CI 1.25-24.85, p=0.02). CONCLUSIONS: Contrary to animal model data, our study suggests MBL deficiency may confer protection against acquiring S. aureus BSI. NOD2 mutations were less frequently associated with multi-organ dysfunction. Further human studies of the innate immune response in S. aureus BSI are needed to identify suitable host targets in sepsis treatment.